The Effect Of Service Journey Quality (Sjq) On Customer Loyalty In Pharmaceutical Retail With Omnichannel Strategy - Gevano, Rahmat; Yuliati, Elevita (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The purpose of this research is to explain how service journey quality (SJQ) affects customer loyalty on pharmaceutical retail with omnichannel strategy. This research focused on SJQ and service quality in pharmaceutical retail and how both affect customer loyalty. The mediating role service quality is assesed between SJQ and customer loyalty. 283 respondents participated in an online questionnaire that distributed using social media and data were analysed through descriptive analysis, validity and reliability test, outer model test, inner model test, and hypothesis test. Inner model and hypothesis test are done by using second order form of SJQ and service quality. All of these test are done for analyze how SJQ affect customer loyalty on pharmaceutical retail.This study found that SJQ cannot directly influence customer loyalty on pharmaceutical retail;s customers, but mediation is needed from good service quality so that SJQ has a positive effect on customer loyalty. The findings from this research can be used as a basis or direction for pharmacists and owners of pharmaceutical facilities on how to manage their pharmaceutical retail business if they have implemented an omnichannel strategy or can also be considered before implementing an omnichannel strategy in their pharmaceutical retail business, both in the form of drugstores and pharmacies.